THE CATHOLIC ENCYCLOPEDIA - Herbermann, Charles G. (edición) (1913)
CONTENIDO: V. 1 AACHEN-ASSIZE. -- V. 2 ASSIZE-BROWNR. -- V. 3 BROW - CLANCY. -- V. 4 CLAND - DIOCESAN. -- V. 5 DIOCESE - FATHERS. -- V. 6 FATHERS - GREGORY. -- V. 7 GREGORY - INFALLIBILITY. -- V. 8 INFAMY - LAPPARENT. -- V. 9 LAPRADE -MASS. -- V. 10 MASS - NEWMAN. -- V. 11 NEW MEXICO - PHILIP. -- V. 12 PHILIP - REVALIDATION. -- V. 13 REVELATION - SIMON STOCK. -- V. 14 SIMONY - TOURNELY. -- V. 15 TOURNON - ZWIRNER ERRATA. -- V. 16 INDEX